Social solidarity movement to prevent the spread of COVID-19 pandemic in Indonesia - Munadhil Abdul Muqsith; Rizky Ridho Pratomo; Ana Kuswanti; Valerii Leonidovich Muzykant (Masyarakat, Kebudayaan dan Politik, 2021)
The COVID-19 pandemic has affected many sectors, especially the health and economic aspects. On the bright side, the potential for social solidarity in the community has been increased. New media technology becomes an oasis in the midst of anxiety when people are forced to distance themselves or carrying out social distancing. Net citizens are using new media technology to raise solidarity and appeal to prevent the spread of COVID-19 from various campaigns on social media. This research aimed to study social movements to prevent the spread of COVID-19 and employed a qualitative approach using content analysis. The results showed that the pandemic triggered the public to take advantage of various social media platforms by creating content about public education and campaigning to raise funds or crowdfunding. It is as if a blessing in disguise when this disaster resulted in the value of collaborative work or gotong-royong that comes from Pancasila, which characterizes the nation’s values so that people are motivated to remind each other to maintain health and also help others to ease the burden of those affected. The analysis of the study by the researchers revealed that public figures dominated this solidarity movement.